Uncovering the specificities of CAD tools for industrial design with design theory – style models for generic singularity. Issue 1 (3rd April 2018) - Arrighi, Pierre-Antoine; Le Masson, Pascal; Weil, Benoit; Kazakçi, Akin
Abstract: According to some casual observers, computer-aided design (CAD) tools are very similar. These tools are used to design new artifacts in a digital environment; hence, they share typical software components, such as a computing engine and human–machine interface. However, CAD software is dedicated to specific professionals – such as engineers, three-dimensional (3D) artists, and industrial designers (IDs) – who claim that, despite their apparent similarities, CAD tools are so different that they are not substitutable. Moreover, CAD tools do not fully meet the needs of IDs. This paper aims at better characterizing CAD tools by taking into account their underlying design logic, which involves relying on recent advances in design theory. We show that engineering CAD tools are actually modeling tools that design a generic variety of products; 3D artist CAD tools not only design but immediately produce single digital artifacts; and ID CAD tools are neither a mix nor an hybridization of engineering CAD and 3D artist CAD tools but have their own logic, namely to create new conceptual models for a large variety of products, that is, the creation of a unique original style that leads to a generic singularity . Such tools are useful for many creative designers beyond IDs.